(untitled) (Journal of Partial Differential Equations, 2021)
Consider (M,g) as a complete, simply connected Riemannian manifold. The aim of this paper is to provide various geometric estimates in different cases for the first eigenvalue of (p,q)-elliptic quasilinear system in both Dirichlet and Neumann conditions on Riemannian manifold. In some cases we add integral curvature condition and maybe we prove some theorems under other conditions.